Payout policy in Brazil: Dividends versus interest on equity - Boulton, Thomas J.; Braga-Alves, Marcus V.; Shastri, Kuldeep (Journal of Corporate Finance, 2012)
We examine the impact of tax burden on cash distribution using a sample of Brazilian firms, which are allowed by law to distribute cash to shareholders in two forms: dividends and tax-advantaged interest on equity. The Brazilian institutional setting is superior to those used in prior studies that examine the choice between dividends and capital gains because, in some cases, dividends provide advantages that outweigh their negative tax consequences, leading firms to rationally choose payout policies that are not optimal when viewed only from the perspective of taxes. We find that taxes are a primary determinant of Brazilian firms’ payout policy decisions, as profitability and payout ratios (nonequity tax shields) are positively (negatively) related to the likelihood that a firm pays interest on equity. However, many firms continue to pay dividends despite the tax advantages of interest on equity payments. Abnormal returns around payout policy announcements suggest that these firms are, at least in part, catering to investor demand.